2016
DOI: 10.1111/1460-6984.12266
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of investigating error profiles in diagnosis of naming impairments

Abstract: Background: Word-retrieval difficulties are commonly experienced by people with aphasia (PwA) and also by typically ageing persons. Differentiation between true naming impairments and naming difficulties found in healthy persons may, therefore, be challenging. Aims: To investigate the extent to which the Maltese adaptation of the Boston Naming Test (BNT) can identify people with lexical retrieval difficulties and to differentiate them from people with unimpaired word finding. Methods & Procedures:Naming perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These errors indicate some degree of successful semantic access, which may reflect a stronger lexical-semantic system and a higher likelihood of successful lexical access in general. The strong positive relationship between semantic error proportions and naming accuracy supports this interpretation and coheres with data suggesting individuals with mild anomia—and even healthy controls, when they make errors—predominantly produce semantic errors ( Grima and Franklin, 2017 ; Nicholas et al, 1989 ; Tallberg, 2005 ). However, this result does not reflect that semantic errors (or mixed errors) are severity-insensitive like some researchers (e.g., Dell et al, 1997 ; Schwartz and Brecher, 2000 ) previously proposed; given the relationship we found, it is unlikely that we would find similar semantic error totals among patients with mild, moderate and severe anomia.…”
Section: Discussionsupporting
confidence: 84%
“…These errors indicate some degree of successful semantic access, which may reflect a stronger lexical-semantic system and a higher likelihood of successful lexical access in general. The strong positive relationship between semantic error proportions and naming accuracy supports this interpretation and coheres with data suggesting individuals with mild anomia—and even healthy controls, when they make errors—predominantly produce semantic errors ( Grima and Franklin, 2017 ; Nicholas et al, 1989 ; Tallberg, 2005 ). However, this result does not reflect that semantic errors (or mixed errors) are severity-insensitive like some researchers (e.g., Dell et al, 1997 ; Schwartz and Brecher, 2000 ) previously proposed; given the relationship we found, it is unlikely that we would find similar semantic error totals among patients with mild, moderate and severe anomia.…”
Section: Discussionsupporting
confidence: 84%
“…Some also consider omission errors as an important sign of aphasia, as they are more likely to occur than semantic errors for some semantic categories (Bormann et al, 2008). Other unique naming error types produced by individuals with stroke-induced aphasia that were not seen in healthy controls include phonologically related nonwords, morphological alterations, perseveration, conduit d'approche (a series of phonologic errors), neologisms, and circumlocutions (Grima & Franklin, 2016;Halai et al, 2018).…”
Section: Word-finding Disorders In Acquired Neurologic Conditionsmentioning
confidence: 99%
“…The classification of errors and the identification of sensitive or potential breakdown points are essential for the early detection of syndromes, their diagnosis and the consequent intervention planning. Grima and Franklin (2017) showed that the presence of atypical errors is key to distinguishing between mild anomic impairments in healthy ageing and those in people with aphasia, an unnoticeable difference in the quantitative test scores. Similarly, Silagi et al (2015) showed that variability in the pattern of errors could help distinguish between controls and mild and moderate AD patients.…”
Section: On the Informativeness Of Errors And Error Types And The Rol...mentioning
confidence: 99%